The stem and progenitor cells and the functional activity of liver from age-different Wistar rats - O. V. Pershina; I. A. Uzyanbaev; A. V. Pakhomova; E. S. Pan; L. V. Kogay; N. N. Ermakova; L. A. Sandrikina; B. K. Kurbatov; V. A. Krupin (Сибирский научный медицинский журнал, 2024)
The liver has a big potential for self-healing, but the activity of regeneration decreases with age. Changes are occurring, including in the functional activity of various liver cell populations, the study of the characteristics of which can become the basis for the development of new therapeutic approaches to the liver diseases treatment at older people. The aim of this research was to study the level of stem and progenitor cells and the functional activity of the healthy liver from age- different rats. Material and methods. Experiments were carried out on Wistar rats aged 6 and 12 months. Ultrasound and histological examination of the liver from rats was used to assess morphological changes. The lipid profile of blood serum was evaluated by biochemical methods. Cytometric methods were used to study the surface and intracellular antigens of stem and progenitor cells isolated from the bone marrow, arterial blood and liver of rats. Results and discussion. In 12-month-old male Wistar rats, compared with 6-month-old rats, excessive formation of extracellular matrix components, disruption of tissue architecture, development of portal hypertension, as well as an increase in the concentration of cholesterol, triglycerides, high- and low-density lipoproteins were revealed. We identified age- related differences in the content of hematopoietic and mesenchymal stem cells, epithelial cells (CD45–CD326+) in the bone marrow, blood and liver of rats. In the liver parenchyma, the populations of hepatocyte precursors (CD45– CD326+CD133+), oval cells (CD45–CD326+CD133+CD90+). At the same time, the level of all cell populations in the liver parenchyma of rats expressing the intracellular marker Sox9 was higher in one-year-old animals compared to younger ones, regardless of the cell phenotype. Conclusions. In the liver of 12-month-old rats, compared to 6-month-old rats, the number of cells expressing Sox9, lymphocytes with an inflammatory phenotype increases, the number of stem cells and various populations of epithelial and endothelial cells decreases, which leads to a decrease in the regenerative capacity of the liver, disruption of the tissue architecture of the organ and changes in lipid metabolism. These changes largely determine the increased susceptibility with age to the development of chronic liver diseases.